Development of porous PLGA/PEI(1.8k) biodegradable microspheres for the delivery of Mesenchymal Stem Cells (MSCs) - Lee, Young Sook (J Control Release, 2015)
Multipotent mesenchymal stem cells (MSCs) promise a therapeutic alternative for many debilitating and incurable diseases. However, one of the major limitations for the therapeutic application of human MSC (hMSC) is the lengthy ex vivo expansion time for preparing a sufficient amount of cells due to the low engraftment rate after transplantation. To solve this conundrum, a porous biodegradable polymeric microsphere was investigated as a potential scaffold for the delivery of MSCs. The modified water/oil/water (W(1)/O/W(2)) double emulsion solvent evaporation method was used for the construction of porous microspheres. PEI(1.8k) was blended with Poly(lactic-co-glycolic acid) (PLGA) to enhance electrostatic cellular attachment to the microspheres. The porous PLGA/PEI(1.8k) (PPP) particles demonstrated an average particle size of 290 µm and an average pore size of 14.3 µm, providing a micro-carrier for the MSC delivery. PPP particles allowed for better attachment of rMSCs than nonporous PLGA/PEI(1.8k) (NPP) particles and non-porous (NP) and porous PLGA (PP) microspheres. rMSC successfully grew on the PPP particles for 2 weeks in vitro. Next, PPP particles loaded with 3 different amounts of hMSC showed increased in vivo engraftment rates and maintained the stemness characteristics of hMSC compared with hMSCs-alone group in rats 2 weeks after intramyocardial administration. These customized PPP particles for MSC delivery are a biodegradable and injectable scaffold that can be used for clinical applications.